THE EXPERIMENTAL INVESTIGATION OF DAMAGED BEAMS REPAIRED WITH REINFORCED JACKETTING - Onal, Mustafa; Kocak, Ali (YILDIZ TECHNICAL UNIV, 2006)
Repair and strengthening of damaged reinforced concerete structural members can be carried out using different techniques. One of these techniques is reinforced concrete jacketting coloums. In practise, reinforced concrete jacketting could be applied to the one side of beams or coloums. Also its different typicals colud be applied to the other sides. In this study, reinforced concerete beams are retrofitted by adding longitudinal reinforcement to the tension side, confining with transverse reinforcement and jacketing with concrete. In this experimental research, six beams were repaired and tested and six beams were used as reference. According to the test results, strength, stifness, ductility and energy absoption capacity of beams were discussed. The parameters which are effective on the behaviour of strengthened beams were determined.
Keywords: Repair and strengthening; beams; damaged; reinforced concrete jacketting; Engineering